Praktik Tasawuf Pada Masyarakat Desa Tanjung Morawa B, Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Fadilah, Subhan; Nasution, Hasan Bakti; Ekowati, Endang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to explore the practice of Sufism in the Tanjung Morawa B Village community, identifying the factors that influence its implementation, as well as its impact on local social and cultural dynamics. Sufism, which is an effort to cleanse the soul and achieve closeness to God, shows the values of wisdom and simplicity in everyday life. This research uses a descriptive analytical method that combines semi-structured interview techniques, non- participant observation, and documentation. Primary data was collected through interviews with Village Heads, religious leaders and local community leaders, as well as through direct observation of Sufism practices. Secondary data was obtained from related documents such as village history, geography and demographic data. The research results show that the people of Tanjung Morawa B Village face challenges from changing times and materialism which often diverts focus from spiritual aspects. However, Sufism teachings such as zuhud still have an important role in reminding people about the balance of life. The practice of Sufism in this village is implemented through the maqamat and ahwal stages, although the community's understanding is not as complex as in big cities. Factors that influence the practice of Sufism in this village include cultural background, the role of religious figures, as well as economic and educational factors. The impact of Sufism practices on social and cultural dynamics in Tanjung Morawa B Village includes increasing the community's spiritual and moral awareness, although modernization and materialism often pose challenges.